2015
DOI: 10.1073/pnas.1423449112
|View full text |Cite
|
Sign up to set email alerts
|

Keap1 regulates inflammatory signaling in Mycobacterium avium -infected human macrophages

Abstract: Several mechanisms are involved in controlling intracellular survival of pathogenic mycobacteria in host macrophages, but how these mechanisms are regulated remains poorly understood. We report a role for Kelch-like ECH-associated protein 1 (Keap1), an oxidative stress sensor, in regulating inflammation induced by infection with Mycobacterium avium in human primary macrophages. By using confocal microscopy, we found that Keap1 associated with mycobacterial phagosomes in a time-dependent manner, whereas siRNA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 53 publications
5
47
1
Order By: Relevance
“…3). However, patient 4 isolates did not show a similar reduction in cytokine production and confirmed the level of variation that has been previously reported (29).…”
Section: Resultssupporting
confidence: 90%
“…3). However, patient 4 isolates did not show a similar reduction in cytokine production and confirmed the level of variation that has been previously reported (29).…”
Section: Resultssupporting
confidence: 90%
“…A study using monocyte derived macrophages (MDM) showed no difference in MDM cytokine responses between patients and controls (104) while a more recent study showed that Keap 1 (an oxidative stress sensor) negatively regulated inflammatory signaling from primary macrophages in MAC infection (105). Other studies of TLR and dectin-based signaling in MAC and MABS infections showed TLR signaling to be crucial (96,(104)(105)(106). In addition, MAPK signaling, ERK1/2 and p38 have been shown to be down regulated in patients with MABS infection with subsequent reduction in TNF, IL6, and IL10 (107).…”
Section: The Immune Response In Pulmonary Ntm Infectionmentioning
confidence: 99%
“…The activation of Nrf2 inhibits the secretion of the Th1 cytokine IFNγ and interleukin (IL)-2 in early events, thereafter promoting CD4+ Th2 differentiation [57,58]. Moreover, Keap1 itself seems to be involved as a positive regulator of NF-κB in inflammatory signaling [59].…”
Section: Resilience Pathways and Immune Systemmentioning
confidence: 99%